Les modules-Fondation Pierre Bergé-Yves Saint Laurent 2010-2015 : Le magazine du Palais de Tokyo. - Bergé, Pierre; Teerlinck, Hilde; de Loisy, Jean; Palais de Tokyo, Paris (Paris : Palais de Tokyo, 2015)
Echard, Mimosa ; Piangiamore, Alessandro ; Ramdani, Samir ; Alsharif, Basma ; Blanchet, Jean-Marie ; Potter, Henrik ; Pône, Elisa ; Kosek, Zdenek ; Badaut Haussmann, Laëtitia ; Van der Auwera, Emmanuel ; Fauget, Sarah ; Martin, Jonathan ; Bouchoucha, Fouad ; et al.
Palais de Tokyo, Paris, tentoonstellingen 2010-2015
boek